Indoor air quality in schools of a highly polluted south Mediterranean area. (19th January 2019) - Ruggieri, Silvia; Longo, Valeria; Perrino, Cinzia; Canepari, Silvia; Drago, Gaspare; L'Abbate, Luca; Balzan, Martin; Cuttitta, Giuseppina; Scaccianoce, Gianluca; Minardi, Remo; Viegi, Giovanni; Cibella, Fabio; et al.
Abstract: This study aimed at surveying lower secondary schools in southern Italy, in a highly polluted area. A community close to an industrial area and three villages in rural areas was investigated. Indoor temperature, relative humidity (RH), gaseous pollutants (CO2 and NO2 ), selected biological pollutants in indoor dust, and the indoor/outdoor mass concentration and elemental composition of PM2.5 were ascertained. Temperature and RH were within, or close to, the comfort range, while CO2 frequently exceeded the threshold of 1000 ppm, indicating inadequate air exchange rate. In all the classrooms, median NO2 levels were above the WHO threshold value. Dermatophagoides p. allergen concentration was below the sensitizing threshold, while high endotoxin levels were detected in the classrooms, suggesting schools may produce significant risks of endotoxin exposure. Concentration and solubility of PM2.5 elements were used to identify the sources of indoor particles. Indoor concentration of most elements was higher than outdoors. Resuspension was responsible for the indoor increase in soil components. For elements from industrial emission (Cd, Co, Ni, Pb, Sb, Tl, V), the indoor concentration depended on penetration from the outside. For these elements, differences in rural vs industrial concentrations were found, suggesting industrial sources may influence indoor air quality nearby schools.